2013
DOI: 10.1515/cclm-2012-0689
|View full text |Cite
|
Sign up to set email alerts
|

Betaine homocysteine methyltransferase (BHMT)-dependent remethylation pathway in human healthy and tumoral liver

Abstract: Carcinogenesis is a multi-step and multifactorial process. It includes genetic, epigenetic, nutritional and environmental factors, which are closely interconnected. Human hepatocellular carcinoma (HCC) is among the most frequent and lethal cancers. Imbalance in the S-adenosylmethionine (SAM) concentration, the main methyl group donor, strongly influences the development of HCC. Key enzymes of carbon metabolism are greatly reduced in patients with cirrhosis and HCC. These alterations play a role in genetic inst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…As a methyl donor, betaine participates in the re-methylation of homocysteine to methionine via the enzyme betaine homocysteine methyltransferase (BHMT) 27 . However, this key enzyme is greatly reduced in HCC patients 29 , and downregulation of BHMT in HCC associates with poor prognosis 30 . Besides, after treating the Hepa 1-6 (derived cells from a mouse HCC model) and E47/C34 cell lines (clones of the HepG2 cell line) with exogenous S-adenosylmethionine (SAM) and betaine, results showed that SAM decreased the number of Hepa 1-6 and E47/C34 cells, and increased the number of dead cells in vitro, while betaine had no significant effect either on the number of surviving cells or dead cells 31 .…”
Section: Discussionmentioning
confidence: 99%
“…As a methyl donor, betaine participates in the re-methylation of homocysteine to methionine via the enzyme betaine homocysteine methyltransferase (BHMT) 27 . However, this key enzyme is greatly reduced in HCC patients 29 , and downregulation of BHMT in HCC associates with poor prognosis 30 . Besides, after treating the Hepa 1-6 (derived cells from a mouse HCC model) and E47/C34 cell lines (clones of the HepG2 cell line) with exogenous S-adenosylmethionine (SAM) and betaine, results showed that SAM decreased the number of Hepa 1-6 and E47/C34 cells, and increased the number of dead cells in vitro, while betaine had no significant effect either on the number of surviving cells or dead cells 31 .…”
Section: Discussionmentioning
confidence: 99%
“…As a methyl donor, betaine participates in the re-methylation of homocysteine to methionine via the enzyme betaine homocysteine methyltransferase (BHMT) [26]. However, this key enzyme is greatly reduced in HCC patients [28], and downregulation of BHMT in HCC associates with poor prognosis [29]. Besides, after treating the Hepa 1-6 (derived cells from a mouse HCC model) and E47/C34 cell lines (clones of the HepG2 cell line) with exogenous S-adenosylmethionine (SAM) and betaine, results showed that SAM decreased the number of Hepa 1-6 and E47/C34 cells, and increased the number of dead cells in vitro, while betaine had no significant effect either on the number of surviving cells or dead cells [30].…”
Section: Discussionmentioning
confidence: 99%
“…Betaine inhibited the proliferation of synovial fibroblasts and SW982 sarcoma cells, but not of HepG2 cells, a hepatic tumour cell line that lost the ability to produce BHMT. 4 This showed that hepatocytes and synovial fibroblasts express BHMT, allowing a folate-independent methionine metabolism. Betaine, in contrast to L-methionine, decreased homocysteine levels.…”
Section: Discussionmentioning
confidence: 99%
“… 2 3 Betaine is involved in the remethylation of homocysteine to synthesise L-methionine, a pathway catalysed by betaine-homocysteine methyltransferase (BHMT). 4 L-methionine and betaine might represent strategies to reverse DNA hypomethylation locally in rheumatoid arthritis (RA) synovial tissue and systemically in peripheral T lymphocytes of patients with RA. 5 However, in RASF, the polyamine recycling pathway excessively consumes SAM, due to an increased expression of spermine/spermidine N1-acetyltransferase (SSAT1), thereby interfering with the DNA methylation process.…”
Section: Introductionmentioning
confidence: 99%